Pengaruh Latihan Ladder Drill Terhadap Kelincahan Pemain Futsal UKM Putri STKIP Muhammadiyah Kuninga - Wirda Vera Yuliawati (Journal of Physical Education and Sport Science, 2023)
ABSTRACTWirda Vera Yuliawati (NIM. 182223118), The Effect of Ladder Drill Exercise on Agility of Women's Futsal Players STKIP Muhammadiyah Kuningan, 2022. This study aims to determine the effect of training using Ladder Drill on the agility of women's Futsal UKM players of STKIP Muhammadiyah Kuningan. This research belongs to the type of pre-experimental research. The design used in this study is the one group pretest posttest design. The population in this study were 15 students who participated in the Women's Futsal UKM STKIP Muhammadiyah Kuningan. The research sample used was 15 players. The sampling technique used is saturated sampling. The instrument that will be used is the agility test at the Illinois Agility Test Track according to Brian Mackenzie. Data collection techniques collected in this study were pre-test and post-test. The data analysis technique in this study used normality test and homogeneity test and hypothesis testing. The results of the study revealed that there was a significant effect of Ladder Drill exercise which was seen in the t-test of 0.000 or it could be interpreted (0.000 < 0.05) that there was an influence from the given training program. From the results of the research that has been done, it can be concluded that the Ladder Drill training method can be developed and applied in the training process to improve agility in the futsal game.